Regionally Selective Atrophy after Traumatic Axonal Injury - Warner, Matthew A (2010)
OBJECTIVES: To determine the spatial distribution of cortical and subcortical volume loss in patients with diffuse traumatic axonal injury and to assess the relationship between regional atrophy and functional outcome. DESIGN: Prospective imaging study. Longitudinal changes in global and regional brain volumes were assessed using high-resolution magnetic resonance imaging (MRI)-based morphometric analysis. SETTING: Inpatient traumatic brain injury unit PATIENTS OR OTHER PARTICIPANTS: Twenty-five patients with diffuse traumatic axonal injury and 22 age- and sex-matched controls. MAIN OUTCOME MEASURE: Changes in global and regional brain volumes between initial and follow-up MRI were used to assess the spatial distribution of post-traumatic volume loss. The Glasgow Outcome Scale – Extended was the primary measure of functional outcome. RESULTS: Patients underwent substantial global atrophy with mean brain parenchymal volume loss of 4.5% (95% Confidence Interval: 2.7 – 6.3%). Decreases in volume (at a false discovery rate of 0.05) were seen in several brain regions including the amygdala, hippocampus, thalamus, corpus callosum, putamen, precuneus, postcentral gyrus, paracentral lobule, and parietal and frontal cortices, while other regions such as the caudate and inferior temporal cortex were relatively resistant to atrophy. Loss of whole brain parenchymal volume was predictive of long-term disability, as was atrophy of particular brain regions including the inferior parietal cortex, pars orbitalis, pericalcarine cortex, and supramarginal gyrus. CONCLUSION: Traumatic axonal injury leads to substantial post-traumatic atrophy that is regionally selective rather than diffuse, and volume loss in certain regions may have prognostic value for functional recovery.